Simple Sentences in Scientific Style - Bitinienė, Audronė (Kalbotyra, 2000)
The article deals with the frequency and distribution of simple sentences and clauses in the scientific style and its sub-styles. In the corpus of 12,000 sentences under the analysis simple sentences were less frequent (44,1%) than complex and compound. In the whole corpus of 6 509 sentences consisting of simple sentences and clauses the simple sentences (24,4%) made up the distinctive feature of sub-styles (variants). In each level of analysis the simple sentences can be described as the point of intersection of distinctive and integrative parameters of scientific style and its sub-styles (variants).